Effect of Seepage Velocity on Formation of Shaft Frozen Wall in Loose Aquifer - Jian Lin; Hua Cheng; Hai-bing Cai; Bin Tang; Guang-yong Cao (Advances in Materials Science and Engineering)
This paper addresses the difficult closure of a frozen wall in a coal mine shaft due to excessive seepage velocity in an aquifer when the aquifer is penetrated via the artificial freezing method. Based on hydrothermal coupling theory and considering the effect of decreased absolute porosity on seepage during the freezing process, a mathematical model of hydrothermal full-parameter coupling with a phase change is created. A shaft is used as a prototype, and COMSOL multiphysics finite element software is employed to perform a numerical simulation of the shaft freezing process at various stratum seepage velocities. The numerical simulation results are verified via a comparison with field measurement data. Based on the numerical simulation results, the impact of various underground water seepage velocities on the artificial frozen wall formation process with the seepage-temperature field coupling effect is analysed. Based on the analysis results, the recommended principles of the optimization design for a freezing plan are described as follows: first, the downstream area is closed to enable the water insulation effect, and second, the closure of the upstream area is expedited to reduce the total closure time of a frozen wall.